Kapasitas VO₂ Max Mahasiswa TPB Olahraga Semester Genap Institute Teknologi Sumatera Tahun 2025: Penelitian - Africo Ramadhani; Boy Sembaba Tarigan; Erny Amalia Lestri; Mahyudi Dwi Septian; Dody Tri Iwandana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the level of VO₂ max capacity in students and provide recommendations for the implementation of TPB Sport learning in higher education. The method used in this quantitative descriptive study with data collection techniques through a 20-meter multistage VO₂ max test. The results showed that of the 50 students taken, 37 students (74%) were in the very poor category, 5 students (10%) were in the poor category, and only 8 students (16%) were in the adequate category. None of the respondents obtained the good or very good category. These results indicate that the VO₂ max capacity of students is generally still low. This low level of fitness can be influenced by a lack of physical activity, daily lifestyle, and unhealthy lifestyles. Therefore, the results of this study are recommended as material for evaluation and improvement in the learning of TPB Sport courses, especially in terms of increasing cardiorespiratory fitness training and education about the importance of physical activity. The conclusion of this study is that the level of VO₂ max capacity in most students is still very low. Of the 50 samples, only 8 individuals were in the adequate category, 5 in the poor category, and 37 in the very poor category.